Usability Assessment of E-Wallet : User Acceptance Testing among Students and Merchants - Missie, Chundau; Hamimah, Ujir; Irwandi, Hipiny (2023)
The primary objective of this research is to evaluate the usability of S Pay Global, a digital wallet application used in Sarawak, through user acceptance testing among UNIMAS students and merchants. To accomplish this, a survey was developed to gather user perceptions related to privacy, security, usability, and other relevant factors. The UTAUT2 construct was adapted for this study, focusing on Performance Expectancy, Effort Expectancy, and Habit, in addition to Perceived Security and Perceived Usefulness. The results of the linear regression analysis indicate that constructs such as Performance Expectancy, Effort Expectancy, Habit, and Perceived Usefulness exhibit a significant association with adoption intention. However, Perceived Security demonstrated a weak or non-existent relationship. Descriptive statistics revealed that the Scan & Pay feature was a crucial component of an e-wallet, followed by a user-friendly, customizable dashboard with an aesthetically pleasing and minimalist design. Although most respondents expressed concerns regarding the non-standard user interface of S Pay Global, recommendations were made for wireframe designs to enhance the application’s usability. These findings provide insights into the development of e-wallet applications and their adoption by users, highlighting the importance of features like Scan & Pay and a user-friendly, customizable dashboard.